The implicit power motive and adolescents’ salivary cortisol responses to acute psychosocial stress and exercise in school - Wegner, Mirko; Schüler, Julia; Schulz Scheuermann, Katharina; Machado, Sergio; Budde, Henning (CNS & Neurological Disorders - Drug Targets, 2015)
In the present study we examined the moderating effect of the power motive on salivary cortisol responses to acute psychosocial stress and exercise in adolescents. Fifty-seven high school students aged M = 14.8 years participated in the study. The Operant Motive Test was applied to measure the implicit power motive and the Personality Research Form was used to measure the explicit power motive. Salivary cortisol levels were assessed before and after the stress stimuli. Participants were randomly assigned to three experimental groups. An exercise group ran 15 minutes at a defined heart rate of 65-75% HRmax. A psychosocial stress group worked on a standard intelligence test for the same amount of time under the assumption, that their test scores will be made public in class after the test. The control group participated in a regular class session. The implicit power motive was significantly associated with increased cortisol levels in the psychosocial stress group. The explicit power motive was not associated with cortisol responses. Findings suggest that the implicit power motive moderates the cortisol responses to acute stress in an adolescent age group with higher responses to psychosocial stress in comparison to exercise or control conditions.
Keywords: Exercise